NCD PATIENT EXPERIENCES ON CHRONIC DISEASE CARE DURING COVID-19 PANDEMIC. A QUALITATIVE CROSS-SECTIONAL STUDY DESIGN STUDY IN TWO SELECTED HEALTH FACILITIES IN MBARARA REGION. - MATSIKO, ADAM; RODRICK, TUGUME; Gladys Nakidde (Student's Journal of Health Research Africa, 2023)
Background: Living with chronic conditions during the COVID-19 pandemic has forced a rapid and dramatic change in where, when and how care is sought to reduce the risk of virus transmission. Several reports have confirmed that COVID-19 patients with pre-existing chronic conditions experience severe disease, worsened health outcomes, and higher mortality than those without Lack of access to healthcare, poor treatment adherence and lack of self-care due to physical/social distancing, lockdowns, and disruption in outpatient services were among the hindrances in the healthcare system despite patients living with chronic diseases requiring maximum attention and easy access to health care for proper monitoring. Therefore, important to explore the patient experiences of chronic disease care during the COVID 19 pandemic in Mbarara region. Methods: This was an exploratory descriptive study with a qualitative approach conducted in randomly selected health centers in Mbarara Region, Southwestern Uganda. People living with chronic diseases receiving care in health facilities around Mbarara Region were purposively sampled for an in-depth interview using an interview guide. Interviews were recorded and transcribed using verbatim in MSWord. The descriptive data analysis was done using Creswell’s six-step model and transcribed by the researcher manually and keywords were identified to represent the codes. Results: Participant experiences during the COVID-19 pandemic were categorized into four themes: lifestyle changes, challenges faced during the lockdown, experiences of the participants diagnosed with COVID-19, preventive measures taken and lessons learnt during the COVID-19 pandemic. Conclusions: People with chronic conditions experienced a confluence of the COVID-19 pandemic and chronic diseases in the context of difficulty in accessing healthcare and in recommendation more research should be done to quantify the factors associated with these patient experiences